The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ijqrm-03-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9001 and ISO/IEC 17025

Abstract: Purpose According to the ISO 9001 standard, all the certified companies should calibrate their measuring equipment. By doing so, companies can guarantee, with rigor and quality, its measurement and use reliable data for monitoring the quality of their products. However, a metrology laboratory is not required to have an ISO 9001 certification or ISO/IEC 17025 accreditation. At this moment, there are companies with their quality management systems certified according to the ISO 9001 standard which have metrology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Concerning implementing management systems in laboratories, it was possible to verify discussions on the quality of management and operations. The articles dealt with the benefits of adopting the ISO 9001 and ISO 17025 standards [49,50], critical analysis [51,52], and even describing implementation steps [52][53][54][55]. Only one article addressed the impact of normative standards [11,40,41,43,56] on chemical analyses activities linked to science and technology [57].…”
Section: Bibliographic Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning implementing management systems in laboratories, it was possible to verify discussions on the quality of management and operations. The articles dealt with the benefits of adopting the ISO 9001 and ISO 17025 standards [49,50], critical analysis [51,52], and even describing implementation steps [52][53][54][55]. Only one article addressed the impact of normative standards [11,40,41,43,56] on chemical analyses activities linked to science and technology [57].…”
Section: Bibliographic Researchmentioning
confidence: 99%
“…It can also be observed that almost half of the laboratory managers (47.6% of private The number of laboratory employees may be considered an impediment to adopting one or more normative systems. Barradas and Sampaio [52] observe that, among the benefits of adopting standard ISO 17025, there is an increase in the number of clients and the resulting increase in the laboratory's workload, which reflects customer's demands for accredited calibrations. This could represent a need to expand the workforce, depending on an analysis of the return on the investment.…”
Section: Field Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…http: //www.ijmp.jor.br v. 11, n. 5, Special Edition IFLOG 2019ISSN: 2236-269X DOI: 10.14807/ijmp.v11i5.1280 and incorporating important aspects of ISO 9001, this accreditation ensures the competence not only of the measurement system but also of the professionals responsible (BARRADAS;SAMPAIO, 2017;INMETRO, 2019;KARTHIYAYINI;RAJENDRAN, 2017).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Data from the Brazilian Calibration Network state that there are about 428 duly certified calibrations and testing laboratories, of which 59 are in the state of Rio de Janeiro, concentrating the second largest quantity in the country (INMETRO, 2019). To guarantee the quality and reliability of the service provided, accreditation is a fundamental step (BARRADAS;SAMPAIO, 2017;INMETRO, 2019). Based on ISO 17025…”
Section: Introductionmentioning
confidence: 99%